Primary internal fixation of fractures of both bones forearm by intramedullary nailing - Singh, RP; Sharma, M (Journal of Institute of Medicine Nepal, 2007)
Background: Both bone fracture of forearm is a common injury, if not treated properly causes severe functional disability to the patients. Materials and Methods: In this study 40 patients each with diaphyseal fractures of both bones forearm treated by square nail were evaluated. Results: Conservative treatment with poor results and prolonged cast immobilization of 2-3 months adds to socio economic burden of patients. Hence various internal fixation devices were developed to achieve good results. Unstable fractures of radius and ulna with subluxation or dislocation of superior or inferior radio-ulnar joints and open fractures with skin loss need internal fixation. Conclusion: Intramedullary nailing is a simple method of treating forearm fractures with better results than conservative methods. Key words: Fracture – Both Bones Forearm Intramedullary Nailing The full text of this paper is available at Journal of Institute of Medicine website